The Influence of Marketing Mix On Customer’s Decisions to do Murabahah Financing at PT. Bank Riau Kepri Syariah (Perseroda) Tanjung Pinang II Branch - Raja Hardiansyah; Nandan Limakrisna; Yudi Julius (Greenation Research & Yayasan Global Resarch National, 2023)
The purpose of this study was to determine the effect of the marketing mix, namely product, price, place, and promotion on the customer's decision to do Murabaha financing at PT. Bank Riau Kepri Syariah (Perseroda) Tanjungpinang II Branch. This study used a sample of 366 customer respondents using a sampling technique, namely purposive sampling. In this study using quantitative methods. The object of this research is a customer of PT. Bank Riau Kepri Syariah (Perseroda) Tanjungpinang II Branch which already has financing. Data collection was carried out in two ways, namely field research and literature study. Respondents filled out a questionnaire consisting of 29 statements related to the variable being measured. The results of this study indicate that the effect of the marketing mix on customer decisions in murabahah financing has varied results. Place variables have a significant influence on customer decisions, while product, price and promotion variables are considered not to have a significant influence on customer decisions in murabahah financing. It can be concluded that from the marketing mix only the place variable partially has a significant enough influence on customer decisions, but simultaneously all marketing mix variables (4p) have a positive and significant effect on customer decisions to do murabahah financing which will have an impact on increasing decisions customers to do murabahah financing at Bank Riau Kepri Syariah (Perseroda) Tanjungpinang II Branch.